Book review. Application of econometrics in economics - Urbina Padilla, Dante Abelardo (2018)
According to Karl Popper, one of 20th century’s greatest philosophers of science, “theories are nets cast to catch what we call ´the world´: to rationalize, to explain, and to master it”. And that is right. Scientists and researchers seek to catch reality by mean of theories. In the case of economics, we seek to catch “economic reality”. We have economic theories. In fact, there are several approaches within economic theory (neoclassical economics, behavioral economics, institutionalism, post-Keynesianism, etc.). But we need specific tools and methods in order to evaluate in a rigorous way the connection between our theories and economic reality. In that context, econometrics become a very important aspect of research in economics.